Testing the validity of EKC hypothesis using CO2 emissions and ecological footprint in Nigeria: The role of financial development - Nadabo, Yusuf Shamsuddeen; Salisu, Suleiman Maigari (Energy Economics Letters, 2025)
This study examines the Environmental Kuznets Curve (EKC) Hypothesis in Nigeria by analysing carbon dioxide emissions and ecological footprint from 1991 to 2022. Using the autoregressive distributed lag (ARDL) bounds test for cointegration and the Toda-Yamamoto causality approach, findings reveal a positive correlation between economic growth and both CO2 emissions and ecological footprint, indicating that environmental impacts rise with economic growth. An inverted U-shaped relationship is observed between economic growth and CO2 emissions, suggesting a threshold beyond which further growth could reduce emissions. Financial development, trade openness, and urbanization significantly influence CO2 emissions and ecological footprint, underscoring the need for sustainable policies. Key recommendations include promoting sustainable urbanization, encouraging green investments through financial regulations, monitoring trade activities, and incentivizing renewable energy adoption. Utilizing green financial products like Sukuk for funding priority infrastructure projects could enhance renewable energy use, environmental sustainability, and financial sector growth in Nigeria. These findings emphasize the urgency for policy interventions to align economic growth with environmental sustainability, ensuring a balanced approach to development while mitigating adverse ecological impacts.